Exploring Methylmercury Demethylation Phenotypes in the Human Gut Microbiome - Drouillard, Jacob (Université d'Ottawa | University of Ottawa, 2024)
Methylmercury, a potent neurotoxicant with global prevalence, poses significant risks to human and ecosystem health. The metabolism of methylmercury still holds many uncertainties, such as the high variability in methylmercury half-lives across individuals. Gut microbiota have been suspected to play a role. This thesis investigated the impact of the human gut microbiome on the demethylation rate of methylmercury. I conducted batch incubations with fecal samples collected from 10 healthy individuals and measured the demethylation rate under different conditions. Their microbiomes were characterized by metagenomic analysis. Results indicate high variability among individual's methylmercury demethylation rate, correlating with pyruvate reduction. Some individuals carried bacterial genes for mercury detoxification, but none of these genes correlated with mercury demethylation. These findings underscore the interplay between diet, gut microbiome, and neurotoxin transformation. This work highlights the link between human microbiome activity and methylmercury metabolism, providing a fresh perspective on neurotoxin exposure modulation.
Keywords: Methylmercury; Microbiome; Toxicology; Metagenomics